Analisis kandungan nitrogen dan fosfor pada sedimen Danau Tondano di area budidaya Toulimembet - Telaumbanua, Yedieli; Tumembouw, Sipriana S.; Watung, Juliaan Ch.; Undap, Suzanne L.; Pangemanan, Pankie L.; Longdong, Sammy N.J. (e-Journal BUDIDAYA PERAIRAN, 2023)
The aim of the research was to analyze the nitrogen and phosphorus content in sediments in the cultivation area of Toulimembet Village. This research method is "survey" determining sampling points "purposive sampling" taking into account that the research location is a fish cultivation area with a floating net system, and data is obtained using primary data and secondary data. Primary data collected were in situ measurements of water quality parameters (temperature, turbidity, TDS, pH, DO) in the Toulimembet Village cultivation area and sediment analysis (Nitrogen and Phosphorus) at the Manado Standardization Research Center Laboratory (BARISTAND). Secondary data was obtained from various sources such as journals and previous research reports. Based on research results in Toulimembet Village, Kakas District, Minahasa Regency, North Sulawesi Province, nitrogen (0.78-1.16%), phosphorus (0.04-0.08%), temperature (25.73-27.01°C), turbidity (4.03-4.90 NTU), TDS (0.160-0.164 g/l), pH (7.89-10.52), DO (7. 20-12.67 mg/L), ammonia (0.07 mg/L), phosphate (0.0030-0.0158 mg/L), nitrite (0.069-0.295 mg/L) are still suitable for cultivation activities. Keywords: Fish culture, water quality, floating net cage, eutrophication